The Persistance and Longevity of Faults in the Crustal Evolution of Southern New Brunswick - O'Brien, Brian. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1977)
Examination of the structural and stratigraphic sequences in southern New Brunswick indicates that the area evolved under the influence of a series of major faults. Relatively localized faulting persisted for at least 450 to S00 Ma. In Part 1 the effects of the faults are systematically outlined over five time intervals beginning in the late Precambrian (Hadrynian), continuing through parts of the Ordovician, Silurian, Devonian and Carboniferous and ending in the Triassic. The relationships of various generations of faults to depositional environments in contemporaneous basins and the regional structural setting are documented. In Part 2 evidence concerning the nature of the major faults and fault zones is presented. Properties peculiar to the southern New Brunswick structures are their repeated association with volcanic rocks, their distinction as narrow zones of stratigraphic and structural discontinuity and their persistant control on the manifestation of stresses associated with repetitive orogeny. Interpretions of the faults are proposed which identify them as long~lived, mechanically weak, dislocation zones in the lithosphere (i.e."deep-faults").